2010
DOI: 10.2220/biomedres.31.319
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of periodontal reattachment on denuded root dentin after periodontal surgery

Abstract: This study evaluates the effects of three kinds of periodontal surgery using statistical analyses of histological and immunohistochemical indices. Dehiscence defects were made on roots of maxillary teeth in monkeys. Surgically exposed roots were untreated, etched with EDTA, or treated with Emdogain ® after EDTA etching. Paraffin sections were stained with hematoxylin and eosin or immunostained for bone sialoprotein (BSP) or osteopontin (OPN) and analysed using several indices. The relative length of regenerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…These two proteins, which participate in initiating mineralization, are believed to play a major role in differentiation of cementoblast progenitor cells to cementoblasts (2). They are reported to be expressed in regenerated cementum, and also their expression is associated with new cementum attachment to dentine surfaces in a monkey model (25). OPN and BSP positive staining in our study indicated that newly formed matrix superficial to cementum was mineralization-related.…”
Section: Discussionsupporting
confidence: 55%
“…These two proteins, which participate in initiating mineralization, are believed to play a major role in differentiation of cementoblast progenitor cells to cementoblasts (2). They are reported to be expressed in regenerated cementum, and also their expression is associated with new cementum attachment to dentine surfaces in a monkey model (25). OPN and BSP positive staining in our study indicated that newly formed matrix superficial to cementum was mineralization-related.…”
Section: Discussionsupporting
confidence: 55%
“…Another possible cause of slit formation is tissue shrinkage during the paraffin sectioning process that can break the weak attachment between these two tissues . Recent studies have shown that bone sialoprotein and osteopontin play a role in adhesion between these two tissues .…”
Section: Discussionmentioning
confidence: 99%
“…Bone sialoprotein is a significant component of mineralized tissues and is localized in cementum and bone . It has been reported that bone sialoprotein mediates the adhesion of cementum to dentin , and bone sialoprotein is considered to take part in cementogenesis along with osteopontin . In addition, bone sialoprotein has been suggested to contribute to PDL remodeling .…”
Section: Discussionmentioning
confidence: 99%